2006
DOI: 10.1111/j.1471-4159.2006.03714.x
|View full text |Cite
|
Sign up to set email alerts
|

ABCA2 is a marker of neural progenitors and neuronal subsets in the adult rodent brain

Abstract: The notion that the ATP-binding cassette transporter-A2 (ABCA2) may be involved in brain sterol homeostasis and is associated with early onset Alzheimer's disease led us to explore its neural expression. Our data support and extend the previous reports on ABCA2 expression by oligodendrocytes. They evidence that ABCA2 (i) is located in intracellular vesicles, identified in transfected cells as lysosome-related organelles only partially overlapping with classical endolysosomes; (ii) is a marker of neural progeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 49 publications
1
38
1
Order By: Relevance
“…Chiba et al [131] suggested that ABCB1 rather than ABCG2 is involved in their "PLC/PRF/5" SP cell phenotype . The published studies on NSCs support the hypothesis that ABCB1 (MDR1) might be more important than ABCG2 in controlling the specific phenotype of NSCs [166][167][168], in contrast to the HSCs where ABCG2 is involved in the SP phenotype and considered as its molecular determinant. In short, ABC transporters have emerged as an important new field of investigation in the regulation of stem cell biology, and manipulation of this system may promote stem cell amplification via a common defence mechanism adopted by these cells through their high expression of ABC membrane transporters [170].…”
Section: A Model For Abc Transporter Expression In Nscsmentioning
confidence: 71%
See 3 more Smart Citations
“…Chiba et al [131] suggested that ABCB1 rather than ABCG2 is involved in their "PLC/PRF/5" SP cell phenotype . The published studies on NSCs support the hypothesis that ABCB1 (MDR1) might be more important than ABCG2 in controlling the specific phenotype of NSCs [166][167][168], in contrast to the HSCs where ABCG2 is involved in the SP phenotype and considered as its molecular determinant. In short, ABC transporters have emerged as an important new field of investigation in the regulation of stem cell biology, and manipulation of this system may promote stem cell amplification via a common defence mechanism adopted by these cells through their high expression of ABC membrane transporters [170].…”
Section: A Model For Abc Transporter Expression In Nscsmentioning
confidence: 71%
“…Recent results show that NSCs from mouse forebrain are contained in a population distinct from the SP [134]. Moreover, other research data show that the ABCA2 transporter is widely expressed in early neural progenitors developed in vitro from ES cells [166]. ABCA2 expression in the adult mouse and rat brains seems to be region-dependent because it is limited to the oligodendrocytic lineage -unambiguously excluded from astrocytes -and to a subset of cortical GABAergic inter-neurons and pyramidal glutamatergic neurons where it could be localized to lysosomal-related organelles [166].…”
Section: Abc Transporters and Nscsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our rationale for asking this question is based on previous studies showing that other ABC transporters including two that, like ABCA7, are also from the "Class-A" subfamily (i.e. ABCA2, ABCA3) appear to play a role in neurogenesis [15,16]. These studies along with the extensive literature highlighting the importance of adult neurogenesis in AD (see [17][18][19][20], for recent comprehensive reviews of this area) prompted our present study in which we have assessed cellular proliferation and neurogenesis in the dentate gyrus (DG) and subventricular zone (SVZ) of both WT and Abca7 − / − adult male mice.…”
Section: Introductionmentioning
confidence: 99%